Correlation of chemical structures of thiazole accelerators with rheokinetic properties of elastomeric compounds - Yu. А. Glebova; А. V. Krylov; V. V. Egorova; V. А. Scherschnev; S. V. Reznichenko; Yu. I. Lyakin (Тонкие химические технологии)
The quantum-chemical calculation of structures of sulfur vulcanization organic thiazole accelerators was performed. It was established that there is a correlation between the atomic electronegativity of nitrogen, the S–N length bond of and the rheokinetic properties of sulfur vulcanizates with Shungite and ZnO as activators. Moreover, scorching time was influenced on type of an activator. It should be noted that in the presence of Shungite under vulcanization began earlier than with ZnO except for MBT. So the strength of the physical adsorption of MBT on the surface of ZnO similars to Shungite.